Central European economic journal
"Central European Economic Journal" is a continuation of a long tradition of issuing scientific journals at the Faculty of Economic Sciences, University of Warsaw. From 2001 to 2016 our journal was published under the title Ekonomia. Rynek, gospodarka, społeczeństwo. During this period it gained an opinion as a leading Polish journal in areas such as experimental economics, mainly due to research results obtained in a local laboratory. In 2016 the decision was taken to change the title and to begin collaboration with De Gruyter Open.